2007
DOI: 10.1021/jf062920s
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Mass Spectrometry Fingerprinting of Brazilian Artisan Cachaça Aged in Different Wood Casks

Abstract: We have investigated the capability of direct infusion electrospray ionization mass spectrometry in the negative ion mode, ESI(-)-MS, to differentiate representative samples of artisan cachaça, a Brazilian sugar cane distillate of large production, aged in four different types of wood casks: amburana (Amburana cearensis), jequitibA (Cariniana estrellensis), balm (Myroxylon peruiferum), and oak (Quercus rubra). The ESI(-)-MS were found to be very characteristic, showing sets of diagnostic ions for each of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 43 publications
1
37
0
4
Order By: Relevance
“…This rapid approach produces a large amount of chemical data that improves selectivity with no significant compromises in reproducibility or accuracy (Dettmer et al 2007). In this study, we applied direct fingerprinting by ESI-Q-ToF-MS. MS fingerprinting analysis has been applied to a variety of biological models and even for bovine embryo culture medium quality control (Sawaya et al 2004, Marques et al 2006, de Souza et al 2007a, 2007b, Souza et al 2008, Ferreira et al 2009, Saraiva et al 2009). Although diverse analytical techniques that are primarily based on spectroscopy technologies, such as near-infrared, RAMAN, and proton NMR, have been used as noninvasive tools to predict embryo viability (Seli et al 2007, Nagy et al 2008, Scott et al 2008, Ahlstrom et al 2011, Hardarson et al 2012, to our knowledge, this is the first report that uses MS fingerprinting to predict human embryo implantation potential.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid approach produces a large amount of chemical data that improves selectivity with no significant compromises in reproducibility or accuracy (Dettmer et al 2007). In this study, we applied direct fingerprinting by ESI-Q-ToF-MS. MS fingerprinting analysis has been applied to a variety of biological models and even for bovine embryo culture medium quality control (Sawaya et al 2004, Marques et al 2006, de Souza et al 2007a, 2007b, Souza et al 2008, Ferreira et al 2009, Saraiva et al 2009). Although diverse analytical techniques that are primarily based on spectroscopy technologies, such as near-infrared, RAMAN, and proton NMR, have been used as noninvasive tools to predict embryo viability (Seli et al 2007, Nagy et al 2008, Scott et al 2008, Ahlstrom et al 2011, Hardarson et al 2012, to our knowledge, this is the first report that uses MS fingerprinting to predict human embryo implantation potential.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in wine have shown that changes during maturation are related with ''bouquet'' characteristic of the product and they, principally, depend on maturation time (Escalona, Birkmyre, Piggott, & Paterson, 2002;Perez-Prieto, LopezRoca, Martinez-Cutillas, Pardo-Minguez, & Gomez-Plaza, 2003), species and geographic origin of wood used in the construction of the barrels (Ancı´n, Garde, Torrea, & Jimenez, 2004;Chatonnet & Dubourdieu, 1998;de Souza et al, 2007;Perez-Coello, Sanz, & Cabezudo, 1999), age of the barrel (Garde Cerda´n, Rodrı´guez Mozaz, & Ancı´n Azpilicueta, 2002;Pe´rez-Prieto, Lo´pez-Roca, Martı´nez-Cutillas, Pardo Mı´nguez, & Go´mez-Plaza, 2002), toasting degree and barrel capacity (Cadahı´a, Ferna´ndez de Simo´n, & Jalocha, 2003;Chatonnet, Cutzach, Pons, & Dubourdieu, 1999;PerezPrieto, Lopez-Roca, Martinez-Cutillas, Pardo-Minguez, & Gomez-Plaza, 2003), the storage conditions such as temperature, the disposition of the barrels, humidity, light, ventilation, as well as the beverage itself (Ceden˜o & Á lvarez-Jacobs, 2003;Garde Cerda´n, Torrea Gon˜i, & Ancı´n Azpilicueta, 2004;Pino, Pe´rez, & Nun˜ez, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in distilled beverages, several investigations have been focused on the evaluation of different factors that might modify favorably or unfavorably the physicochemical characteristics and composition of some spirits such as sake (Isogai, Utsunomiya, Kanda, & Iwata, 2005), cachac¸a (de Souza et al, 2007), cider distillates (Mangas, Rodriguez, Moreno, & Blanco, 1996a), rum (Pino et al, 1996), and tequila (Mun˜oz-Mun˜oz, Grenier, Gutie´rrez-Pulido, & CervantesMartı´nez, 2008), among others, during maturation. For tequila in particular, several studies have been directed to the use of different methodologies that have allowed separating and identifying a great number of volatile compounds in the stages of cooking, fermentation and distillation (Arellano, Pelayo, Ramirez, & Rodriguez, 2008;Carreon-Alvarez et al, 2011;Mancilla-Margalli & Lopez, 2002;Mora´n-Marroquı´n, Co´rdo-va, Valle-Rodrı´guez, Estarro´n-Espinosa, & Dı´az-Montan˜o, 2011;Prado-Ramı´rez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Existe, portanto, a necessidade declarada de avaliar as propriedades sensoriais e os possíveis efeitos sobre a saúde humana do emprego de madeiras brasileiras no envelhecimento de cachaças. 9,[14][15][16][17][18][19][20] A classificação de uma árvore, matéria-prima para a produção de tonéis, é realizada considerando principalmente os seus órgãos reprodutores (flores e frutos) e, também, outras características morfológicas da árvore (casca, folhas, etc.) e mesmo em alguns casos a análise do seu aroma.…”
Section: Introductionunclassified
“…22 Aos esforços nesta direção somam-se recentemente as aplicações de técnicas quimiométricas a banco de dados provenientes das aplicações de diferentes técnicas instrumentais a extratos de madeiras e de produtos de origem vegetal. 16,17 Como parte dos esforços para o desenvolvimento da análise quí-mica da aguardente, neste trabalho são apresentados resultados sobre a aplicação da técnica espectrofotométrica (UV) com tratamento quimiométrico dos espectros eletrônicos para a caracterização de extratos de 4 espécies de madeiras da flora brasileira e do carvalho. Os dados aqui reportados foram comparados aos resultados obtidos a partir de perfis cromatográficos (CLAE-DAD), anteriormente descritos 16 para estas amostras, objetivando a elaboração de um procedimento de rotina para a identificação de extratos hidroalcoólicos de madeiras com base na espécie empregada.…”
Section: Introductionunclassified